Prevalence of Health-Risk Behaviors and Mental Well-Being of ASEAN University Students in COVID-19 Pandemic - Rahman, Hanif Abdul; Amornsriwatanakul, Areekul; Abdul-Mumin, Khadizah H.; Agustiningsih, Denny; Chaiyasong, Surasak; Chia, Michael; Chupradit, Supat; Huy, Le Quang; Ivanovitch, Katiya; Nurmala, Ira; Majid, Hazreen B. Abdul; Nazan, Ahmad Iqmer Nashriq Mohd; et al. (MDPI stays neutra, 2022)
The prevalence of epidemiological health-risk behaviors and mental well-being in the COVID-19 pandemic, stratified by sociodemographic factors in Association of South East Asian Nations (ASEAN) university students, were examined in the research. Data were collected in March–June 2021 via an online survey from 15,366 university students from 17 universities in seven ASEAN countries. Analyzed data comprised results on physical activity, health-related behaviors, mental well-being, and sociodemographic information. A large proportion of university students consumed sugar-sweetened beverages (82.0; 95CI: 81.4, 82.6) and snacks/fast food daily (65.2; 95CI: 64.4, 66.0). About half (52.2; 95CI: 51.4, 53.0) consumed less than the recommended daily amounts of fruit/vegetable and had high salt intake (54; 95CI: 53.3, 54.8). Physical inactivity was estimated at 39.7 (95CI: 38.9, 40.5). A minority (16.7; 95CI: 16.1, 17.3) had low mental well-being, smoked (8.9; 95CI: 8.4, 9.3), and drank alcohol (13.4; 95CI: 12.8, 13.9). Country and body mass index had a significant correlation with many health-risk behaviors and mental well-being. The research provided important baseline data for guidance and for the monitoring of health outcomes among ASEAN university students and concludes that healthy diet, physical activity, and mental well-being should be key priority health areas for promotion among university students. © 2022 by the authors.